EFL students’ anxiety and reading comprehension - Riana, Lulut; Ningrum, Yusnita Sylvia (ELT Forum: Journal of English Language Teaching, 2025)
Reading comprehension is a very important basic skill in learning English as a Foreign Language (EFL), as it strongly supports students' overall academic success. However, many EFL learners struggle to understand reading texts due to emotional barriers, especially anxiety. This article presents a narrative literature review examining the relationship between EFL srudents’ reading anxiety and their reading comprehension. It synthesizes findings from national and international studies published between 2017 to 2025. The review is based on in two theoretical framworks:  Krashen’s Affective Filter Hypothesis, which highlights the role of emotional factors, such as anxiety, motivation, and self-confidence in second language acquisition; and Constructivist Learning Theory, which emphasizes the importance of learners actively constructing knowledge through cognitive factors in language learning. The review identifies several common causes of reading anxiety, such as unfamiliar vocabulary, complex sentence structures, low self-confidence, and negative prior experiences. Anxiety not only disrupts reading comprehension but also affects students’ motivation, self-esteem, and willingness to read. The findings highlight the importance of addressing students’ emotional need during reading instruction. Teachers are encouraged to adopt supportive strategies, such as simplifying reading materials, providing encouragement, and fostering a safe environment. This article concludes with a call for further empirical research to explore effective teaching practice that can reduce reading anxiety and enhance comprehension in EFL contexts.